Design and Evaluation of a Mudharabah-Based Dairy Goat Investment Model - Nicholas Renaldo; Achmad Tavip Junaedi; Suhardjo Suhardjo; Amries Rusli Tanjung; Sri Indrastuti; Umar Faruq; Sulaiman Musa; Nabila Wahid (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
The livestock sector plays a strategic role in strengthening food security, rural income generation, and sustainable agribusiness development in emerging economies. However, access to capital remains a critical constraint for small-scale livestock farmers, particularly under conventional interest-based financing systems that impose rigid repayment obligations amid biological and market uncertainties. This study aims to design and evaluate a mudharabah-based dairy goat investment model by integrating Islamic contract principles with livestock production economics. Using a quantitative financial feasibility modeling approach, the study simulates a one-year partnership contract incorporating milk revenue sharing, offspring profit allocation, biological production cycles, risk mitigation mechanisms, and monthly return distribution. Financial performance is assessed using Return on Investment (ROI), Net Present Value (NPV), and Payback Period, complemented by sensitivity analysis under optimistic, moderate, and pessimistic scenarios. The results indicate that the dual-revenue mudharabah model generates positive returns, maintains financial feasibility under moderate production variability, and enhances liquidity through periodic income distribution. From a theoretical perspective, the study extends Agency Theory by demonstrating that profit-sharing mechanisms improve incentive alignment and reduce agency costs, while operationalizing Islamic Contract Theory into a measurable agribusiness investment framework. The findings suggest that mudharabah-based livestock investment offers an economically viable, sharia-compliant, and socially inclusive financing alternative for sustainable rural development.